2013
DOI: 10.1021/ie3030714
|View full text |Cite
|
Sign up to set email alerts
|

Facile Tailoring of Anatase TiO2 Morphology by Use of H2O2: From Microflowers with Dominant {101} Facets to Microspheres with Exposed {001} Facets

Abstract: A facile hydrothermal route employing H2O2 as structure-directing agent was explored to fabricate anatase microflowers with dominant {101} facets and anatase microspheres with exposed {001} facets. The influence of H2O2 concentration on crystal structure, morphology, and facet composition of TiO2 was investigated in detail. H2O2 plays a crucial role in determining the crystal structure, morphology, and exposed facets of TiO2. The presence of H2O2 favors the formation of anatase phase. When the concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…As a result, the obtained anatase TiO 2 consists of {101} and {001} exposed facets. 23 When the F − ion is present, the surface energy of (110) surface decreases dramatically, because of the strong adsorption ability of F − ion. As the concentration of H 2 O 2 increases, the surface energy of (001) reaches the value of (101) firstly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the obtained anatase TiO 2 consists of {101} and {001} exposed facets. 23 When the F − ion is present, the surface energy of (110) surface decreases dramatically, because of the strong adsorption ability of F − ion. As the concentration of H 2 O 2 increases, the surface energy of (001) reaches the value of (101) firstly.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of H 2 O 2 and HF, the titanium in Ti(OC 3 H 7 -i) 4 would be converted into Ti-F and peroxo-titanium structures. 23 Since the main difference between TiCl 4 (or TiCl 3 ) and Ti(OC 3 H 7 -i) 4 lies in the presence/absence of chlorine ion, the enlargement of {110} facets using TiCl 3 (or TiCl 4 ) as titanium source should be ascribed to the influence of Clion. Based on the above and previous experiment results, 15,16,19,23 we summarized the influences of titanium source, H 2 O 2 , Cl − , and HF on the composition of exposed facets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…under acidic conditions [24,26], which would retard the hydrolysis for the Ti 3+ /Ti 4+ -containing precursors. The surface energy for {0 0 1} facets are undermined by increasing H 2 O 2 concentration due to enhanced adsorption of PTCs on the {0 0 1} surface [27]. Therefore, the slow diffusion of PTCs in the solution and subsequent hydrolysis process kinetically drives the formation of vertex-truncated octahedra containing exposed {0 0 1} facets.…”
Section: Resultsmentioning
confidence: 99%
“…Surface plasmon resonance absorption is associated with a significant enhancement of the electric near field in the vicinity of the Au nanoparticles. It was reported that the enhanced near-field could boost the excitation of electron-hole pairs in TiO 2 or other semiconductors and therefore sustaining the photochemical reaction [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. At last, the influence of the gold deposition procedure on the structural and photocatalytic properties should be considered, and this is another factor affecting the photocatalytic efficiency of the Au-TiO 2 composite.…”
Section: Resultsmentioning
confidence: 99%